Industrial and Engineering Chemistry. Industrial Edition (Raston, Eschenbach printing company, 1935-1970)
The journal was established in 1909 as the Journal of Industrial & Engineering Chemistry. It was renamed in 1930 as Industrial & Engineering Chemistry before obtaining its current title in 1970 Industrial & Engineering Chemistry Research.